A protocol independent energy saving technique for mobile ad hoc networks. (10th July 2006) - Gadallah, Yasser; Kunz, Thomas
In this study, we present PIES, an energy saving technique for mobile ad hoc networks (MANET). PIES works in conjunction with existing routing protocols to help those protocols make energy conservation decisions without changing their core functionality. PIES is designed to achieve energy fairness amongst network nodes. Its functionality is distributed and does not depend on any single node or set of nodes within the network. Simulations show that PIES can generate energy savings of about 50% and extends the lifetime of the network by about 70%. PIES also performs well with both on-demand and proactive routing protocols.